A Business Plan On the Establishment of Apeeling Burger Business (ABB) in #13 Susano Road, Novaliches Proper, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Apeeling Burger Business (ABB) offers burgers made from banana peel as the mainingredient in the patty instead of meat, catering to health-conscious customers who enjoydelicious food. This burger concept was established in February 2023 and will open inAugust 2023. It is located at #13 Susano Road, Novaliches Proper, Quezon City, with acapital of Php50,000.00 and five employees. The investment expenditure will be dividedamong the five owners in a specific ratio. Burgers are a popular option for Filipinos on the godue to their price and convenience.The marketing plan divides Apeeling Burger Business (ABB) 's target market into segmentsbased on demographic, geographic, psychographic, behavioral, and socioeconomic factors.ABB develops business goals and engages with the target market or customer tounderstand their precise demands. Apeeling Burger Business’ (ABB) co-owners will be theirown employees. Apeeling Burger Business’ (ABB) employees are appointed based on theirexperience with appropriate roles and responsibilities. The results show that providingcustomers with healthy meals at a reasonable price, a friendly environment, adaptableworkers, and social media engagement are all essential to ensuring their contentment.Due to its anticipated favorable financial plan in terms of an income statement, cash flow,and balance sheet, Apeeling Burger Business (ABB) can accomplish its long-term goals andcan draw investors.
Keywords: Business Administration